AESTHETIC VALUE IN TITLE IN “HUJAN BULAN JUNI” BY SAPARDI DJOKO DAMONO AND “MALAIKAT JUGA TAHU” BY DEWI LESTARI - Hendrike Priventa (Multilingual, 2020)
Poetry is a form of literary genre that is full of aesthetic values. The aesthetic value is wrapped in the elements that make up the poetry. This article discusses a comparison of the aesthetic value of the poem “Hujan Bulan Juni” by Sapardi Djoko Damono and “Angels Also Know” by Dewi Lestari. Intertext studies can be used as a medium to find aesthetic values and determine whether literary works are aesthetic or not. The aesthetic value in the poetry "Rain in June" and "Angels Also Know" are shown in several aspects, namely the elements of sound, diction, and image. The linkage of authorship is also shown through the expansion of the use of elements of the poetry structure. The aesthetic value in both poems influences the process of forming new vehicles such as songs and films which are now more popular with the public.